2020
DOI: 10.1097/sle.0000000000000877
|View full text |Cite
|
Sign up to set email alerts
|

Easily Applicable Single-incision Laparoscopic Appendectomy Using Straightforward Instrumental Alignment and Conventional Laparoscopic Instruments

Abstract: Background: Laparoscopic appendectomy is one of the most frequently performed operations. As such, single-incision laparoscopic appendectomy (SILA) is indicated as a feasible and safe procedure comparable to conventional laparoscopic appendectomy (CLA). However, novice surgeons face challenges in performing SILA, because the role of the surgeon's hands is reversed. We introduce an easily applicable technique of SILA by adapting the alignment of CLA.Methods: A series of 61 consecutive patients underwent SILA be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Finally, 17 research articles or case series on SPLA, from the Republic of Korea, China, India, Spain, and other countries, were included in the present review. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Most articles were from the Republic of Korea (n ¼ 6), followed by China (n ¼ 4), India (n ¼ 3), Vietnam (n ¼ 1), Argentina (n ¼ 1), Egypt (n ¼ 1), and Spain (n ¼ 1). There were eight retrospective studies, six prospective studies, and three case series (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 17 research articles or case series on SPLA, from the Republic of Korea, China, India, Spain, and other countries, were included in the present review. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Most articles were from the Republic of Korea (n ¼ 6), followed by China (n ¼ 4), India (n ¼ 3), Vietnam (n ¼ 1), Argentina (n ¼ 1), Egypt (n ¼ 1), and Spain (n ¼ 1). There were eight retrospective studies, six prospective studies, and three case series (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Surgical techniques, equipment, and devices, including magnet-assisted single trocar (MAST), needle grasper (Endo Relief)-assisted single-incision laparoscopic appendectomy (NASILA), and SPLA using a needle-type grasping forceps (SLAN) are summarized (Table 1). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The performance of each technique was also compared in terms of clinical outcomes (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgeons tend to use less invasive techniques when managing acute appendicitis. Although single-incision LA is more attractive due to less abdominal wall trauma, faster recovery ( 24 ), and better cosmetic results compared to CLA ( 15 ). Moreover, Markar et al ( 25 ) found in their meta-analysis that the incidence of wound infection was reported in all the included studies, with 4% in each group and no statistical difference between the two techniques.…”
Section: Discussionmentioning
confidence: 99%